2019
DOI: 10.1158/1541-7786.mcr-18-0748
|View full text |Cite
|
Sign up to set email alerts
|

Periprostatic Adipose Tissue Favors Prostate Cancer Cell Invasion in an Obesity-Dependent Manner: Role of Oxidative Stress

Abstract: Prostate gland is surrounded by periprostatic adipose tissue (PPAT), which is increasingly believed to play a paracrine role in prostate cancer progression. Our previous work demonstrates that adipocytes promote homing of prostate cancer cells to PPAT and that this effect is upregulated by obesity. Here, we show that once tumor cells have invaded PPAT (mimicked by an in vitro model of coculture), they establish a bidirectional crosstalk with adipocytes, which promotes tumor cell invasion. Indeed, tumor cells i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 49 publications
3
79
0
Order By: Relevance
“…Until now, studies showed that metabolic exchanges between adipocytes and tumor cells require a close proximity between the two cell types in order for tumors to provoke adipocyte lipolysis. For most types of cancer, this process can only occur at the later stages of cancer progression, when tumors become invasive and penetrate local AT or metastasize to adipocyte-rich environments (Nieman et al, 2011;Wang et al, 2017;Zhang et al, 2018;Laurent et al, 2019). However, whether adipocytes could also influence tumors at distance, for example, during the early stages of disease progression before cancer cells infiltrate surrounding adipose tissue, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, studies showed that metabolic exchanges between adipocytes and tumor cells require a close proximity between the two cell types in order for tumors to provoke adipocyte lipolysis. For most types of cancer, this process can only occur at the later stages of cancer progression, when tumors become invasive and penetrate local AT or metastasize to adipocyte-rich environments (Nieman et al, 2011;Wang et al, 2017;Zhang et al, 2018;Laurent et al, 2019). However, whether adipocytes could also influence tumors at distance, for example, during the early stages of disease progression before cancer cells infiltrate surrounding adipose tissue, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In many solid tumors occurring in organs with particularly abundant fat, the surrounding adipose tissue is often invaded by cancer cells, thus enabling close contact with adipocytes at the tumor invasive front [9][10][11][12]. Invading cells are indeed able to actively interact with the surrounding adipocytes and deeply modify both their phenotype and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, studies showed that metabolic exchanges between adipocytes and tumor cells requires a close proximity between the two cells types in order for tumors to provoke adipocyte lipolysis. For most types of cancer, this process can only occur at the later stages of cancer progression, when tumors become invasive and penetrate local AT or metastasize to adipocyte-rich environments (Laurent et al, 2019;Nieman et al, 2011;Wang et al, 2017;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%